The synthesis and pharmacology of some novel excitatory amino acid analogues - Badman, G. T. (1986)
Certain amino acids, notably L-glutamate and L-aspartate, are believed to fulfil a role as excitatory neurotransmitters in the mammalian Central Nervous System (CNS). Investigation has revealed the presence of three, and possibly a fourth, type of receptor for such neurotransmitters. These receptors have been named after the most potent and selective agonist of each; thus they are usually referred to as N-methyl-D-aspartate (A1), quisqualate (A2), kainate (A3) and 2-amino, 4-phosphono butyric acid (A4); the designations in brackets being that of the nomenclature of Fagg and Foster.